Pathway outta pigeonhole? De-contextualizing Majority World Countries. (January 2021) - Cheruiyot, David; Ferrer-Conill, Raul
Should regional context overshadow theoretical contributions of a doctoral dissertation or an international journal article? In this essay, we argue that expendable region-centricism diminishes the contributions of Majority World Countries to the media and communication discipline. We propose that 'de-contextualized' studies – which accentuate the theoretical, conceptual, or methodological import of research – could complement current efforts to decentre knowledge.